PEMALSUAN IDENTITAS DALAM PERNIKAHAN KEDUA DILAKUKAN OLEH ANGGOTA DPRD PROVINSI KALIMANTAN TIMUR - Fitri Yuliani (Journal of Law ( Jurnal Ilmu Hukum ), 2021)
ABSTRACT               This study aims to determine the application of identity falsification sanctions in the second marriage carried out by members of the East Kalimantan Province Dprd. The problem raised in this paper is to determine the application of identity forgery sanctions in the second marriage carried out by members of the Dprd. This research uses empirical research. The research data is in the form of primary data obtained from direct research in the field consisting of primary, secondary and tertiary legal materials. The results of this study indicate that the identity falsification after investigating the perpetrator is still married but faking his identity is a widower or a divorcee. Therefore, the perpetrator is charged under Law Number 24 of 2013 concerning Population Administration in Article 94 Any person who orders and / or facilitates and / or manipulates Population Data and / or Population data elements as referred to in Article 77 shall be sentenced to imprisonment. a maximum of 6 (six) years and / or a fine of not more than IDR 75,000,000.00 (seventy five million rupiah).               The verdict handed down by the Court against the Defendant was fair because in this case the Defendant admitted that the act he had committed violated the law, namely falsification of identity and before making this decision the court had also considered things that were burdensome and mitigating.Keywords: Identity Falsification, DPRD Members